KEMAHIRAN MENULIS AKADEMIK MAHASISWA BARU INSTITUT TEKNOLOGI SAWIT INDONESIA MELALUI PENGKAJIAN BERBASIS PENELITIAN PADA MATA KULIAH BAHASA INDONESIA - Anggraini Barus, Friska; Mardiah, Mardiah (Jurnal Bahtera: Jurnal Pendidikan, Bahasa, Sastra, dan Budaya, 2025)
This study aims to measure the academic writing skills of new undergraduate students at the Indonesian Palm Oil Institute (ITSI) through a research-based assessment approach in the General Indonesian Language course. The research method used a one-group pretest-posttest design. Participants were 30 new students from the Class of 2024 enrolled in the odd semester. Data collection instruments included an academic writing test, a rubric observation sheet, and a student response questionnaire. Data analysis was conducted quantitatively (paired t-test) and qualitatively (thematic analysis of writing results). The results showed a significant increase in academic writing scores (pretest M=58.20; posttest M=75.80; t(29)=8.45; p <0.001). Qualitative findings revealed developments in aspects of structure, grammar, and use of research sources. Based on the findings, it was concluded that research-based assessment is effective in improving the academic writing skills of new students at ITSI..